2020
DOI: 10.1007/s10555-020-09914-6
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based inhibitor design of mutant RAS proteins—a paradigm shift

Abstract: As a member of small GTPase family, KRAS protein is a key physiological modulator of various cellular activities including proliferation. However, mutations of KRAS present in numerous cancer types, most frequently in pancreatic (> 60%), colorectal (> 40%), and lung cancers, drive oncogenic processes through overactivation of proliferation. The G12C mutation of KRAS protein is especially abundant in the case of these types of malignancies. Despite its key importance in human disease, KRAS was assumed to be non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 84 publications
(128 reference statements)
0
24
0
4
Order By: Relevance
“…9). 45 On the basis of these findings, we propose the choice of the second-line drug(s) depending on the secondary mutations that emerge on acquiring resistance (Fig. 6B).…”
Section: Discussionmentioning
confidence: 98%
“…9). 45 On the basis of these findings, we propose the choice of the second-line drug(s) depending on the secondary mutations that emerge on acquiring resistance (Fig. 6B).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, we found that the SP2 inhibitor site is only present in structures with Y71 exposed to solvent, while the SP12 inhibitors site appears in structures with Y71 buried into the protein core. Although this trend for Y71 was previously described for a select few SP12 inhibitor-bound structures 8,38 , the consistency of this finding among many inhibitor-bound structures suggests it is an essential determinant of SP2 and SP12 druggability.…”
Section: Discussionmentioning
confidence: 49%
“…Importantly, the presence of SP12 and SP2 sites correlated with different side chain χ1 (chi1) dihedrals (i.e., rotamers) for residue Y71 in SW2. The SP12 inhibitor-bound structures prefer a ~60°, or gauche-plus (g+) rotamer of Y71, which buries Y71 within the RAS domain, exposing the SP12 site and occluding the SP2 site; this trend for Y71 was previously described for a select few SP12 inhibitor-bound structures 8,38 . The SP2 inhibitor -bound structures, by contrast, contain a ~300°, or gauche-minus (g-) rotamer of Y71, which exposes Y71 to solvent thereby opening the SP2 site and occluding the SP12 site (Fig.…”
Section: Sw1 and Sw2 Conformations Associated With Biological Ras Int...mentioning
confidence: 54%
See 1 more Smart Citation
“…Recently, many studies have focused on attempts that target exchange nucleotide. Recent studies have focused on attempts to block nucleotide exchange [ 8 , 9 ]. Several structure-based inhibitors (e.g., SML-8-73-1, H-REV107 peptide, BAY-293, or BI-3406) have been reported to target the guanine nucleotide binding site of the KRAS mutant and inhibit GDP to GTP exchange [ 10 , 11 , 12 , 13 ].…”
Section: Structurementioning
confidence: 99%